(untitled) (Research, Society and Development, 2021)
Objective: to reflect on the propagation of fake news related to carbon dioxide contamination by the use of face masks in prevention of COVID 19. Methodology: study with a qualitative, exploratory and descriptive approach, of a reflection study type, based on publications on the theme and fake news about possible harm caused by the use of masks during the COVID 19 pandemic, which currently afflicts the world. Also, search for scientific articles and books. Results: the results showed that the use of masks of any kind is not related to hypoxia due to the supposed reabsorption of carbon dioxide from cell metabolism, even in people with comorbidities and undergoing physical exercise. Conclusion: it is necessary to prove the effectiveness of the use of masks, paying attention to social awareness, demystifying the fake news associated with science, especially in relation to hypoxemia.